The impact of value added tax, petroleum profit tax and government spending on non-oil exports - Umar Bala; Hiakewe Doolamen Magdalene; Rabiu Maijamaa; Hahuza Adamu Haruna (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2023)
This study examined the impact of fiscal policy on non-oil exports in the Nigerian economy. Annual time series data were used from 1980 to 2021. The cointegration link was verified using the autoregressive and distributed lag (ARDL) bound test. The results show that three elements of fiscal policy the value added tax, the petroleum profit tax, and government spending have a considerable long-term impact on non-oil export. The study also found that exports of goods other than oil were negatively and significantly impacted by domestic debt. Furthermore, exports other than oil are determined to have little economic impact. As a result, the study recommends that the government concentrate its efforts on diversifying the economy and government revenue, as doing so will make borrowing loans from other countries easier. The government must diversify its revenue sources away from oil and capitalize on the non-oil sector's ability to create small and medium-sized jobs.